Evaluation of inflammatory and biochemical markers in COVID-19 patients treated with tocilizumab alone or with the combination of tocilizumab and convalescent plasma transfusion (Annals of Medical Research, 2022)
Aim: Macrophage activation syndrome (MAS) develops due to increased expression of systemic pro-inflammatory cytokines in patients with the 2019 novel coronavirus disease (COVID-19). Immune modulators have been used in anti-cytokine therapy, with the hypothesis that they can ensure cytokine inhibition and treat cytokine storm.  The present study aimed to evaluate inflammatory and prognostic biomarkers in severe COVID-19 cases treated with tocilizumab (TCZ) alone or with the combination of tocilizumab and convalescent plasma transfusion (CPT).Materials and Methods: In this retrospective study, data archives of patients with severe acute respiratory syndrome coronavirus 2 (SARS-Cov-2) and who were treated with TCZ alone or the combination of CPT and TCZ were evaluated in line with the literature. The obtained data were statistically evaluated and the alpha significance value was taken as
Keywords: Atlizumab; Convalescent plasma; Macrophage activation syndrome; Tocilizumab